(untitled) (MAUSAM, 1971)
During the winter season cloud and precipitation belts are seen to move from west to east over northern India. The cause of these cloud and precipitation systems came to be referred to as ’western disturbances’. In this study the cloud systems have been classified into five broad categories. Typical examples of these cloud patterns and synoptic conditions most commonly associated with each category of cloud systems are presented in this paper.